2001
DOI: 10.1002/bies.1050
|View full text |Cite
|
Sign up to set email alerts
|

The DAP kinase family of pro‐apoptotic proteins: novel players in the apoptotic game

Abstract: The DAP (Death Associated Protein) kinase family is a novel subfamily of pro-apoptotic serine/threonine kinases. All five DAP kinase family members identified to date are ubiquitously expressed in various tissues and are capable of inducing apoptosis. The sequence homology of the five kinases is largely restricted to the N-terminal kinase domain. In contrast, the adjacent C-terminal regions are very diverse and link individual family members to specific signal transduction pathways. There is increasing evidenc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
54
0
2

Year Published

2003
2003
2023
2023

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 92 publications
(56 citation statements)
references
References 47 publications
0
54
0
2
Order By: Relevance
“…However, melanoma tumors are notoriously resistant to apoptosis mediated by diverse insults (reviewed by Serrone and Hersey, 1999). The death-associated protein kinase (DAP-kinase) is a calcium/calmodulin-regulated serine/threonine kinase that localizes to the cytoskeleton, participates in several apoptotic processes (reviewed by Kogel et al, 2001) and is a tumor suppressor (Kissil and Levy-Strumpf and Kimchi, 1998;Raveh and Kimchi, 2001). Is SKI involved in the resistance to apoptosis of melanoma cells?…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…However, melanoma tumors are notoriously resistant to apoptosis mediated by diverse insults (reviewed by Serrone and Hersey, 1999). The death-associated protein kinase (DAP-kinase) is a calcium/calmodulin-regulated serine/threonine kinase that localizes to the cytoskeleton, participates in several apoptotic processes (reviewed by Kogel et al, 2001) and is a tumor suppressor (Kissil and Levy-Strumpf and Kimchi, 1998;Raveh and Kimchi, 2001). Is SKI involved in the resistance to apoptosis of melanoma cells?…”
Section: Perspectives and Future Directionsmentioning
confidence: 99%
“…Developing a panel of methylation markers may therefore have value in early detection of cancer precursors, provide added reassurances of safety for women who are candidates for less frequent screens, and predict outcomes of women infected with carcinogenic human papillomavirus infections [5]. In this analysis, we evaluated methylation in cervical cancer and CIN3 using a candidate panel of five genes: TNFRSF10C, an antiapoptotic receptor of the TRAIL (TNF-related apoptosisinducing ligand) pathway lacking death domain decoys [6]; death-associated protein kinase (DAPK1) [7]; SOCS3, a suppressor of cytokine signaling [8]; heparan sulfate D-glucosamyl 3-O-sulfotransfarase-2 (HS3ST2), which encodes an enzyme involved in the final modification step of heparan sulfate proteoglycans (HSPGs) [9]; and CDH1, an adhesion molecule [10] Previous studies have shown that these genes are frequently methylated in cervical cancers and tumors of other organ sites whereas aberrant methylation was not detected in a limited number of normal cervical tissues tested [6][7][8][9][10]. The aim of the present study was to evaluate methylation of these five a priori candidate genes in a convenience sample of invasive cervical cancer tissues and residual liquid-based cytology specimens confirmed by expert review as CIN3.…”
Section: Introductionmentioning
confidence: 99%
“…ZIPK is involved in the regulation of apoptosis, cell motility and contractility, and mitosis, particularly cytokinesis. In these contexts, ZIPK seems to function primarily as a myosin light chain kinase or, during mitosis, as a histone kinase (for reviews and references, see Ko¨gel et al, 2001;Haystead, 2005;Scheidtmann, 2007). A role of ZIPK in transcription is supported from its interactions with transcription and splicing factors ATF4, AATF and CDC5 (Kawai et al, 1998;Page et al, 1999a, b;Engemann et al, 2002), and its colocalization with PML bodies (Ko¨gel et al 1999;Kawai et al, 2003).…”
Section: Introductionmentioning
confidence: 99%